Pelatihan Pengembangan Karir Untuk Meningkatkan Komitmen Organisasi Kader Partai X Dewan Pimpinan Cabang Kabupaten Sleman - Riyan Betra Delza; Alimatus Sahrah (LPPM Universitas Proklamasi 45, 2021)
Organizational commitment in political parties is the most important element to support the achievement of political parties. Therefore, in maintaining the stability and achievement of political parties, organizational commitment to party members is important to be maintained and enhanced. This study aims to determine the increase in organizational commitment through career development training. Career development training consists of two aspects, namely career planning and career management. This career development training has seven sessions namely self assessment, Exploring opportunities, making decisions and goal settings, planning for the achievement of achievement goals and career management. Characteristics of the subjects of this study are party administrators who have a low and medium category of organizational commitment. The design used is the Pretest-Posttest Control Group. The hypothesis of this study is that there are differences in organizational commitment among party cadres between before and after career development training. Then in the second hypothesis, there is a difference in the level of posttest organizational commitment between the experimental group and the control group. While the data analysis uses the Mann Whitney test and the Wilcoxon test. Experimental results based on the Mann Whitney test found Z = -3,585 (p <0.01), meaning that there was a difference in posttest scores between the experimental group that was given training and the control group that was not given training, meaning the hypothesis (1) was accepted. Based on the Wilcoxon test it was found there was a difference between the organizational commitment score in the experimental group between before and after being given career development training with Z = -1836 (p <0.01) meaning the hypothesis (2) was accepted.